Release layer composition, release film and their manufacturing method, as well as film laminate and method of using same

JP7631839B2Active Publication Date: 2025-02-19MITSUBISHI CHEM CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021011419
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-27
Publication Date
2025-02-19
Estimated Expiration
2041-01-27

AI Technical Summary

Benefits of technology

【0009】 本発明が提案する離型層組成物及び離型フィルムは、離型層を形成するための(A)架橋性フッ素シリコーンポリマーが、少なくとも2種類以上併用されることにより、シリコーン粘着剤層に対して軽剥離性と低移行性を有する。また、本発明が提案する離型フィルムの製造方法によれば、そのような離型層組成物及び離型フィルムを好適に製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631839000001
    Figure 0007631839000001
  • Figure 0007631839000002
    Figure 0007631839000002
  • Figure 0007631839000003
    Figure 0007631839000003
Patent Text Reader

Abstract

To provide a novel release film that is easy to peel from silicone pressure-sensitive adhesive layer, has excellent light-release property, and has low migration property.SOLUTION: Provided is a release layer composition that contains at least two (A) crosslinkable fluorine silicone polymers different from each other.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a release layer composition, a release film and methods for producing the same, as well as a film laminate and a method for using the same. [Background technology]

[0002] In recent years, the number of automobiles equipped with liquid crystal panels has been increasing. In-vehicle applications such as these are often exposed to high and low temperatures for long periods of time, so the adhesive used to bond the panel components is also required to have high weather resistance and heat resistance. Silicone adhesives, which are primarily made of silicone, are attracting attention as an adhesive that meets this requirement.

[0003] Silicone adhesives have excellent heat resistance, chemical resistance, and transparency, and are characterized by their ability to adhere to materials that are difficult to adhere to with general adhesives, such as silicone rubber, fluororesin, and metals, as well as excellent re-adhesiveness. Silicone adhesives are used in the form of tapes (films) with the adhesive layer as the adhesive. Before use, they are usually stored with one or both sides covered with a release film, and when in use, the release film is peeled off.

[0004] As the release film used for this type of application, a silicone release film which is obtained by coating a base film with a silicone release agent is widely used. However, when such a silicone release film is coated with a silicone adhesive, the adhesive and the release film tend to adhere strongly to each other, making them difficult to peel off, because the chemical structures of the release agent and the adhesive are similar. Therefore, in order to reduce the peel strength of the silicone adhesive (to make it easier to release), fluorine has been introduced into the silicone release agent. For example, Patent Document 1 proposes a fluorinated silicone material having a fluorine substituent to exhibit release properties against the silicone adhesive. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2011-201035 A Summary of the Invention [Problem to be solved by the invention]

[0006] The crosslinkable fluorine silicone polymer disclosed in Patent Document 1 is a substance with high chemical stability and low toxicity. However, in order to make the release film coated with the crosslinkable fluorine silicone polymer easier to release, the coating thickness is often increased, which is disadvantageous in terms of cost. Furthermore, the silicone release agent using the fluorine silicone polymer may migrate to the adhesive, etc., causing a decrease in the adhesive strength of the adhesive or causing contamination of the adherend to which the adhesive is adhered.

[0007] Therefore, the present invention relates to a silicone release film formed using a fluorinated silicone, and it is an object of the present invention to provide a new release agent composition that has easy releasability and low migration towards a silicone pressure-sensitive adhesive layer, a release film, and a film laminate that includes the release film, and a method for using the same. [Means for solving the problem]

[0008] As a result of extensive investigations, the present inventors have found that the above problems can be solved by using a release layer composition and a release film having specific configurations, and have completed the present invention as described below. That is, the present invention provides the following [1] to

[27] . [1] A release layer composition comprising at least two different crosslinkable fluorine-containing silicone polymers (A). [2] The release layer composition according to the above [1], which combines (A) crosslinkable fluorine silicone polymers that differ in at least one of the ratio of fluorine substituents, the structure of the fluorine substituents, and the viscosity or weight average molecular weight. [3] The release layer composition according to [1] or [2] above, further comprising (B) a silicone crosslinking agent and (C) a curing catalyst. [4] The release layer composition according to any one of the above [1] to [3], which contains a silicone crosslinking agent (B) that does not contain a fluorine substituent. [5] The release layer composition according to any one of the above [1] to [4], in which at least one kind of (A) crosslinkable fluorine silicone polymer is subjected to a crosslinking reaction in advance in a blend liquid, and then at least another (A) crosslinkable fluorine silicone polymer is mixed therein. [6] A release film comprising: a base film; and a release layer formed on at least one side of the base film by curing the release layer composition according to any one of [1] to [5] above. [7] The release film according to the above [6], wherein the fluorine atom content in the release layer is 3,000 ppm by mol or more and 900,000 ppm by mol or less. [8] The release film according to [6] or [7] above, wherein the adhesive peel strength of the release layer is 500 mN / cm or less and the residual adhesive strength is 3300 mN / cm or more. [9] A method for producing a release layer composition, comprising mixing (A) a crosslinkable fluorine-silicone polymer, (B) a silicone crosslinking agent, and (C) a curing catalyst, and then mixing another (A) crosslinkable fluorine-silicone polymer different from the (A) crosslinkable fluorine-silicone polymer.

[10] The method for producing a release layer composition described in [9] above, wherein the other (A) crosslinkable fluorine silicone polymer is different in at least one of the ratio of fluorine substituents, the structure of the fluorine substituents, and the viscosity or weight average molecular weight.

[11] A method for producing a release layer composition according to the above [9] or

[10] , comprising mixing (A) a crosslinkable fluorine-containing silicone polymer, (B) a silicone crosslinking agent, and (C) a curing catalyst, followed by stirring and / or allowing to stand, and then mixing in the other (A) crosslinkable fluorine-containing silicone polymer.

[12] The method for producing a release layer composition according to the above

[11] , wherein the stirring and / or standing is performed for 1 minute or more.

[13] The method for producing a release layer composition according to any one of the above [9] to

[12] , wherein the (B) silicone crosslinking agent is a silicone crosslinking agent that does not contain a fluorine substituent.

[14] A method for producing a release film, comprising applying the release layer composition obtained by the method for producing a release layer composition according to any one of the above items [9] to

[13] to at least one side of a substrate film.

[15] A film laminate comprising the release film according to any one of [6] to [8] above, a silicone pressure-sensitive adhesive layer, and a laminate film having a functional layer, the release film and the laminate film having the functional layer being bonded together via the silicone pressure-sensitive adhesive layer.

[16] The film laminate according to the above

[15] , wherein the laminate film having a functional layer comprises a base film and a crosslinked resin layer provided on at least one side of the base film.

[17] The film laminate according to the above

[16] , wherein the crosslinked resin layer is formed from a crosslinked resin layer composition containing a conductive polymer and a binder polymer.

[18] The film laminate according to the above

[16] , wherein the crosslinked resin layer is an easy-adhesion layer for the silicone adhesive layer.

[19] The film laminate according to any one of the above

[15] to

[18] , wherein the laminate film having a functional layer comprises a base film and another release layer provided on one side of the base film.

[20] The film laminate according to

[19] above, wherein the other release layer is configured to sequentially comprise: (E) a first layer formed from a silicone composition containing as a main component a silicone polymer that does not contain a fluorine substituent; and a second layer containing a component that has a fluorine substituent.

[21] The film laminate according to

[19] above, wherein the other release layer is formed from a silicone composition containing (A) a cross-linkable fluorine-containing silicone polymer as a main component.

[22] The film laminate according to

[19] above, wherein the other release layer is formed from a silicone composition containing, as a main component, (E) a silicone polymer not containing a fluorine substituent.

[23] A film laminate comprising the release film according to any one of [6] to [8] above, a silicone pressure-sensitive adhesive layer, and a resin film, wherein the resin film is directly bonded to the release film via the silicone pressure-sensitive adhesive layer.

[24] A film laminate comprising the release film according to any one of [6] to [8] above, a silicone pressure-sensitive adhesive layer, and a heavy release film, wherein the release film is laminated on one side of the silicone pressure-sensitive adhesive layer and the heavy release film is laminated on the other side of the silicone pressure-sensitive adhesive layer, and the heavy release film has a peel strength higher than that of the release film, the method comprising peeling off the release film, attaching the exposed surface of the silicone pressure-sensitive adhesive layer to an adherend, and then peeling off the heavy release film.

[25] The method for using the film laminate according to the above

[24] , wherein the adherend is an optical component.

[26] A method for using the film laminate according to the above

[24] or

[25] , wherein the optical component is a polarizing plate or a touch sensor.

[27] A method for using the film laminate according to any one of

[25] or

[26] above, wherein the optical component is an optical component for use in a vehicle. Effect of the Invention

[0009] The release layer composition and release film proposed by the present invention have light releasability and low migration to the silicone pressure-sensitive adhesive layer by using at least two or more types of (A) crosslinkable fluorine silicone polymers in combination to form the release layer. Moreover, according to the production method of the release film proposed by the present invention, such a release layer composition and release film can be suitably produced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will now be described based on the embodiments, although the present invention is not limited to the embodiments described below.

[0011] <Release Layer Composition> The release layer composition of the present invention contains at least (A) a crosslinkable fluorine-containing silicone polymer.

[0012] ((A) Crosslinkable Fluorosilicone Polymer) The (A) crosslinkable fluorine-containing silicone polymer can impart stable and easy releasability to silicone pressure-sensitive adhesives. Incidentally, "silicone" is a polyorganosiloxane whose backbone (siloxane backbone) is a siloxane bond (≡Si-O-Si≡) consisting of silicon and oxygen, with organic groups mainly composed of methyl (-CH3) bonded to the silicon (Si). A "crosslinkable fluorine silicone polymer" is a silicone that can be cured through a crosslinking reaction by heating or exposure to light (ultraviolet rays).

[0013] The term "fluorosilicone polymer" refers to a silicone polymer having a substituent containing a fluorine atom. The fluorine atom-containing substituent (fluorine substituent) is not particularly limited as long as the substituent contains a fluorine atom. Specific examples include a fluorine group, a trifluoromethyl group, a pentafluoroethyl group, a 2,2-trifluoroethyl group, a 1H,1H-heptafluorobutyl group, a 2H-hexafluoroisopropyl group, a perfluoro-t-butyl group, and a perfluorohexyl group. In addition, it may be a monovalent hydrocarbon group having an ether bond and a fluorine atom, and may be a fluorine substituent having a fluorine-containing polyalkylene oxide structure such as a fluorine-containing polypropylene oxide structure. However, it is not limited to these. Furthermore, examples of components having a fluorine substituent include polyorganosiloxanes that contain a fluorine substituent in the side chain portion of the polymer backbone. In (A) the crosslinkable fluorine silicone polymer, the ratio of fluorine substituents among the functional groups (hereinafter also referred to as "R") directly bonded to Si that constitutes the siloxane skeleton is, for example, 5 to 35 mol %, and preferably 10 to 30 mol %.

[0014] In the (A) crosslinkable fluorine silicone polymer, R directly bonded to Si may be an unsubstituted or substituted monovalent hydrocarbon group. The monovalent hydrocarbon group may be a monovalent hydrocarbon group substituted with a fluorine atom (i.e., a fluorine substituent), or may have an ether bond. As described above, the fluorine substituent may have an ether bond. As described later, the monovalent hydrocarbon group may be a monovalent hydrocarbon group having an alkenyl group. The carbon number of the monovalent hydrocarbon group is, for example, 1 to 15 carbon atoms, and preferably 1 to 10 carbon atoms.

[0015] In the present invention, the use of a curable silicone that cures via a hydrosilylation addition reaction is preferred from the standpoint of material availability, particularly in the case of "(A) cross-linkable fluorine-based silicone polymer." Therefore, it is preferable that the (A) crosslinkable fluorine silicone polymer has at least two alkenyl groups.Here, examples of the alkenyl group include vinyl group (ethenyl group), allyl group (2-propenyl group), butenyl group, pentenyl group, hexenyl group, heptenyl group, octenyl group, and decenyl group, and among these, vinyl group is preferable.These alkenyl groups are preferably silicon atom-bonded alkenyl groups when directly bonded to the Si that constitutes the siloxane skeleton. In the crosslinkable fluorine-containing silicone polymer (A), the ratio of alkenyl groups among the functional groups (hereinafter also referred to as "R") directly bonded to Si that constitutes the siloxane skeleton is, for example, 0.2 to 10 mol %, and preferably 0.5 to 5 mol %.

[0016] In addition, examples of the monovalent hydrocarbon group of R include, in addition to the above-mentioned alkenyl group and fluorine substituent, an alkyl group, an aryl group, etc. Examples of the alkyl group include an alkyl group such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a t-butyl group, an isobutyl group, and a sec-butyl group. Examples of the aryl group include a phenyl group, a tolyl group, etc. As described above, R should be mainly methyl groups, and in the crosslinkable fluorine-based silicone polymer (A), for example, 50 mol % or more of R should be methyl groups, preferably 55 to 94 mol %, and more preferably 65 to 89 mol %.

[0017] Specific examples of the crosslinkable fluorine silicone polymer include KP-911, X-70-201S, and X-41-3035 manufactured by Shin-Etsu Chemical Co., Ltd., and FS1265-300CS, FS1265-1000CS, FS1265-10000CS, BY24-900, BY24-903, 3062, Q2-7785, SYL-OFF 7792, and SYL-OFF 7795 manufactured by Dow Corning Toray Co., Ltd., but are not limited thereto.

[0018] (A) crosslinkable fluorine silicone polymer may be a solvent type, a solventless type, or a mixture of these. (A) crosslinkable fluorine silicone polymer must be used in a mixture of two or more types to achieve light release.

[0019] Here, "solventless curing silicone" refers to a silicone with a viscosity that allows it to be applied without diluting it with a solvent, and is made up of short polysiloxane chains and has a relatively low molecular weight. The viscosity of the solvent-free curing silicone is 30,000 mm when dissolved in 85% by mass of n-heptane at 25°C. 2 / s or less, and especially 20,000 mm 2 / s or less is preferable, and 10,000 mm 2 / s or less is more preferable. 2 / s or more is preferable, 500 mm 2 / s or more is even more preferable.

[0020] On the other hand, "solvent-curable silicone" is a silicone with a relatively high molecular weight that is too viscous to be applied without diluting it in a solvent. Therefore, solvent-curable silicone generally has a lower weight-average molecular weight or viscosity than solventless-curable silicone. The viscosity here refers to the viscosity measured under the same conditions, for example, the viscosity at 25°C when dissolved in an organic solvent such as n-heptane or diisopropyl ether at the same concentration.

[0021] The viscosity of solvent-curable silicone at 25°C is 0.1 mm when it is dissolved in 10% diisopropyl ether. 2 / s or more is preferable, and 0.5 mm 2 / s or more is more preferable, and 1.0 mm 2 / s or more is more preferable, and 300 mm 2 / s or less is preferable, and 200 mm 2 / s or less is preferable, and 100 mm 2 The solvent-curable silicone has a high viscosity, and therefore tends to have a high adhesion to the substrate film. In addition, the term "solventless curable silicone" refers to silicones with low viscosity as described above, and does not necessarily have to be solvent-free, and may be diluted with a solvent and then blended into the release layer composition. Similarly, the term "solvent-curable silicone" does not necessarily have to be diluted with a solvent and then blended into the composition.

[0022] The fluorine atom content (atomic number fraction) of a crosslinkable fluorosilicone polymer is generally on the order of several thousand ppm (less than 1% of the total number of atoms in the "crosslinkable fluorosilicone polymer") to several hundred thousand ppm (several tens of percent of the total number of atoms in the "crosslinkable fluorosilicone polymer").

[0023] The release layer composition of the present invention contains at least two different types of (A) crosslinkable fluorine silicone polymers. By containing two or more types of (A) crosslinkable fluorine silicone polymers, the release layer composition of the present invention has light releasability to the silicone pressure-sensitive adhesive layer and can achieve low migration, and can increase the residual adhesive strength of the pressure-sensitive adhesive after the release sheet is peeled off, for example. Although the principle behind this is not clear, it is presumed that, by containing two or more types of (A) cross-linkable fluorine silicone polymer, the polymer components having fluorine atoms are unevenly distributed, and the highly hydrophobic components tend to be unevenly distributed near the surface, and that this unevenly distributed state is stably maintained by appropriate cross-linking, etc.

[0024] Specifically, it is preferable to use a combination of at least two or more types of (A) crosslinkable fluorine silicone polymers that differ in at least one of the ratio of fluorine substituents, the structure of the fluorine substituents, and the viscosity or weight average molecular weight. By differing in one or more of these, components with different release properties and crosslinkability are mixed in the composition, making it easier to ensure light release properties and low migration. When the structures of the fluorine substituents are different, it is preferable that the difference be at least in the length (that is, the number of carbon atoms) of the fluorine substituents and the presence or absence of a branched structure. One or more of these may be different, but for example, two or more may be different. For example, two or more types of (A) crosslinkable fluorine silicone polymers that differ in both the ratio of fluorine substituents and the viscosity or weight average molecular weight may be used.

[0025] In addition, as the two or more (A) crosslinkable fluorine silicone polymers having different viscosities or weight average molecular weights, a combination of solventless curable silicone and solvent curable silicone can be mentioned. In this case, the solventless curable silicone and the solvent curable silicone may have the same ratio of fluorine substituents and the same structure of fluorine substituents, but it is preferable that at least one of them is different. For example, when the ratio of fluorine substituents is different, it is preferable to make the ratio of fluorine substituents of the solventless curable silicone lower than that of the solvent curable silicone. The details of the case where the solventless curable silicone and the solvent curable silicone are used together are as described above. Furthermore, by using a solventless type and a solvent type in combination as described above, the viscosity of the coating liquid can be reduced, and a release layer having a good coat appearance and small thickness variation can be formed.

[0026] (Blending ratio) In the release layer composition, the mass ratio of the (A) cross-linkable fluorine-silicone polymer (first (A) component) to another (A) cross-linkable fluorine-silicone polymer (second (A) component) of a type different from the first (A) component is preferably 1:50 to 10:1, more preferably 1:20 to 5:1, even more preferably 1:10 to 2:1, and even more preferably 1:5 to 1:1. Although not particularly limited, a solvent-curable silicone may be used as the first component (A), and a solventless-curable silicone may be used as the second component (A). The ratio of fluorine substituents in the first (A) component may be higher than that in the second (A) component, for example. In this case, the difference in ratio may be, for example, about 1 to 15 mol%, preferably about 2 to 12 mol%, and more preferably about 4 to 10 mol%. In this way, if the first (A) component is a solvent-curable silicone or has a high ratio of fluorine substituents, it will be difficult to crosslink; however, as described below, it will be properly crosslinked by pre-crosslinking through prior treatment, making it easier to achieve both low peelability and low migration.

[0027] ((B) Silicone Crosslinker) The release layer composition preferably contains (B) a silicone crosslinking agent in addition to the above-mentioned (A) crosslinkable fluorine silicone polymer. The "crosslinking agent" is a compound that links silicone polymers such as (A) the crosslinkable fluorine silicone polymer to each other, and is, for example, a compound that can link two or more molecules by a chemical covalent bond.

[0028] Examples of the silicone crosslinking agent include (B1) a silicone crosslinking agent that does not contain a fluorine substituent (also referred to as a "non-fluorinated silicone crosslinking agent") and (B2) a silicone crosslinking agent that contains a fluorine substituent (also referred to as a "fluorinated silicone crosslinking agent"). In the present invention, there is no particular restriction as to whether to use the non-fluorinated silicone crosslinking agent (B1) or the fluorinated silicone crosslinking agent (B2), but from the viewpoint of ensuring the effect of the pre-reaction described below, increasing the uneven distribution of fluorine, i.e., increasing the light peelability, and increasing the residual adhesive strength, it is particularly preferable to use the non-fluorinated silicone crosslinking agent (B1). The non-fluorinated silicone crosslinking agent (B1) may be used alone, or may be used in combination with the fluorinated silicone crosslinking agent (B2).

[0029] ((B1) Non-fluorinated silicone crosslinker) The (B1) non-fluorinated silicone crosslinking agent is represented by the following general formula (1), and is preferably one having at least 2, preferably 3 or more (usually about 3 to 200), more preferably 3 to 100, and particularly preferably 3 to 50 silicon-bonded hydrogen atoms (SiH groups) in one molecule.

[0030] R b H c SiO (4-b-c) / 2 (1)

[0031] In formula (1), R is an unsubstituted or substituted monovalent hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 10 carbon atoms, b is 0.7 to 2.1, particularly 0.8 to 2.0, c is 0.001 to 1.0, and b+c is a positive number that satisfies 0.8 to 3.0, particularly 1.0 to 2.5.

[0032] Here, R may be the same group as R of the (A1) crosslinkable fluorine silicone polymer, but preferably has no aliphatic unsaturated bond, such as an alkenyl group. Preferred examples include an alkyl group and an aryl group. Details of the alkyl group and the aryl group are as described above.

[0033] The silicon-bonded hydrogen atoms may be bonded to silicon atoms at the ends of the molecular chain, or to silicon atoms in the middle of the molecular chain (non-terminal portions of the molecular chain), or to both.

[0034] The molecular structure of the non-fluorinated silicone crosslinking agent (B1) may be any of linear, cyclic, branched, and three-dimensional network structures. Furthermore, the number of silicon atoms in one molecule (or degree of polymerization) is preferably 2 to 3,000, more preferably 3 or more, and particularly preferably 4 or more, and is more preferably 2,000 or less, more preferably 1,000 or less, and particularly preferably 500 or less.

[0035] (B1) Non-fluorinated silicone crosslinking agents include tris(dimethylhydrogensiloxy)methylsilane, tris(dimethylhydrogensiloxy)phenylsilane, 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, methylhydrogencyclopolysiloxane, methylhydrogensiloxane-dimethylsiloxane cyclic copolymer, methylhydrogenpolysiloxane capped with trimethylsiloxy groups at both ends, dimethylsiloxane-methylhydrogen capped with trimethylsiloxy groups at both ends, Siloxane copolymer, dimethylpolysiloxane capped at both ends with dimethylhydrogensiloxy groups, methylhydrogenpolysiloxane capped at both ends with dimethylhydrogensiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymer capped at both ends with dimethylhydrogensiloxane, methylhydrogensiloxane-diphenylsiloxane copolymer capped at both ends with trimethylsiloxy groups, methylhydrogensiloxane-diphenylsiloxane-dimethylsiloxane copolymer capped at both ends with trimethylsiloxy groups, (CH3)2HSiO 1 / 2 Units and SiO 4 / 2 A copolymer consisting of (CH3)2HSiO units. 1 / 2 Units and SiO 4 / 2 Units and (C6H5)SiO 3 / 2 and copolymers consisting of these exemplified compounds in which some or all of the methyl groups have been substituted with other alkyl groups such as ethyl groups and propyl groups, or aryl groups such as phenyl groups, but are not limited thereto. It is preferable to use two or more types of crosslinking agents in combination, in order to expect the effect of promoting the crosslinking reaction.

[0036] The content of (B1) non-fluorinated silicone crosslinking agent (the total amount when multiple types are used) is preferably 0.05 to 25 parts by mass, more preferably 0.1 part by mass or more, and even more preferably 0.2 part by mass or more, relative to 100 parts by mass of (A) crosslinkable fluorine silicone polymer, and is more preferably 20 parts by mass or less, even more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less.

[0037] Specific examples of the (B1) non-fluorinated silicone crosslinking agent include 3062A, 3062B, 3062D, and SP 7297 manufactured by Dow Corning Toray Co., Ltd.

[0038] ((B2) Fluorinated silicone crosslinker) On the other hand, the (B2) fluorinated silicone crosslinking agent can be exemplified by the (1) formula, in which at least a portion of R is a group having a fluoro group. Examples of the group having a fluoro group include the above-mentioned fluorine substituents. The other configurations of the (B2) fluorinated silicone crosslinking agent are the same as those described for the (B1) non-fluorinated silicone crosslinking agent, except that at least a portion of R is a group having a fluoro group, and the description thereof will be omitted. Specific examples of the fluorinated silicone crosslinking agent include 3062C and Q2-7560 manufactured by Dow Corning Toray Co., Ltd. The content of the (B2) fluorinated silicone crosslinking agent is preferably 0.1 to 50 parts by mass, more preferably 0.3 parts by mass or more, and even more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the (A) crosslinkable fluorinated silicone polymer. Also, the content is preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less.

[0039] The molar ratio of silicon-bonded hydrogen atoms (SiH groups) in the silicone crosslinker (B) to the total amount of silicon-bonded alkenyl groups in the crosslinkable fluorine silicone polymer (A) is preferably 0.3 to 3.0, more preferably 0.5 or more, and even more preferably 0.8 or more, and is more preferably 2.5 or less, and even more preferably 2.0 or less.

[0040] ((C) Curing catalyst) The release layer composition more preferably contains, in addition to the silicone crosslinker (B), a curing catalyst (C). The "curing catalyst" is a catalyst for promoting the hydrosilylation addition reaction between the silicon-bonded alkenyl groups of the crosslinkable fluorine silicone polymer (A) and the hydrogen silane (SiH) groups of the silicone crosslinker (B). Examples of the curing catalyst include platinum-based catalysts such as platinum black, platinic chloride, chloroplatinic acid, a reaction product of chloroplatinic acid with a monohydric alcohol, a complex of chloroplatinic acid with an olefin, platinum group metal catalysts such as platinum bisacetoacetate, palladium catalysts, and rhodium catalysts, but are not limited to these.

[0041] The content of the curing catalyst in the release layer composition is preferably 0.5 to 500 ppm by mass, more preferably 5 ppm by mass or more, and even more preferably 10 ppm by mass or more, more preferably 500 ppm by mass or less, and even more preferably 200 ppm by mass or less, calculated as the metal amount relative to the total amount of the (A) crosslinkable fluorosilicone polymer.

[0042] (D) Reaction control agent The release layer composition and the present release layer may contain a reaction inhibitor in addition to the above components, if necessary.

[0043] As the reaction inhibitor (D), acetylene alcohol represented by the following general formula (2) can be used.

[0044] CH≡CC(R2)(OH)R1(2)

[0045] In formula (2), R1 is a linear or branched monovalent hydrocarbon group having 5 to 15 carbon atoms, and R2 is a linear monovalent hydrocarbon group having 1 to 3 carbon atoms.

[0046] In the above formula (2), R1 is preferably a linear or branched monovalent hydrocarbon group having 5 to 15 carbon atoms, more preferably 6 to 14 carbon atoms, and even more preferably 8 to 12 carbon atoms. Specific examples of R1 include alkyl groups such as pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, and dodecyl, and alkenyl groups such as pentenyl, hexenyl, and heptenyl, but are not limited to these. In the above formula (2), when the carbon number of the monovalent hydrocarbon group of R1 is 5 or more, the volatility of the control agent is low and sufficient control effect is obtained. On the other hand, when the carbon number is 15 or less, the effective component of acetylene alcohol per mole is reduced, and the control effect is prevented from being weakened, and it is not necessary to add a large amount to obtain the desired control effect.

[0047] In the above formula (2), R2 is a linear monovalent hydrocarbon group having 1 to 3 carbon atoms, preferably 1 to 2. Specific examples of R2 include alkyl groups such as methyl, ethyl, and n-propyl groups, and alkenyl groups such as vinyl, allyl, and n-propenyl groups. However, the examples are not limited to these. The fewer the carbon atoms in R2, the easier it is to achieve the control effect of the silicone composition, and a methyl group is preferable.

[0048] The reaction inhibitor may be used alone or in combination of two or more kinds, if necessary. The content of the reaction inhibitor is preferably 0.001 to 5.0 parts by mass per 100 parts by mass of the present release layer composition, more preferably 0.01 parts by mass or more, even more preferably 0.05 parts by mass or more, more preferably 1.0 parts by mass or less, and even more preferably 0.5 parts by mass or less. Note that "100 parts by mass of the release layer composition" means 100 parts by mass of the solid content in the release layer composition excluding volatile components (solvents), and the same applies below.

[0049] ((E) Silicone polymer containing no fluorine substituents) The release layer composition may further contain (E) a silicone polymer that does not contain fluorine substituents. The silicone polymer not containing a fluorine substituent may be a solvent-based or solventless type, or a mixture of these. Among these, from the viewpoint of obtaining stable easy releasability to silicone pressure-sensitive adhesives, it is preferable that the silicone polymer not containing a fluorine substituent (E) is a solvent-curable silicone.

[0050] Specific examples of silicone polymers not containing fluorine substituents include KNS-3051, KNS-320A, KNS-316, KNS-3002, KNS-3300, X-62-1387, KS-837, X-62-2829, KS-3650, KS-847, KS-847T, KS-776L, KS-776A, KS-774, KS-3703T, KS-3601, KS-830E, X-62-2825, X-62-9201-A, X-62-9201B, KM3951, KM-768, X-52-6015, KF-2005, and X-62-720 manufactured by Shin-Etsu Chemical Co., Ltd. 5, X-62-7028-A, X-62-7028-B, X-62-7052, X-62-7622, ​​X-62-7660, X-62-7655; SP7017, SP7015, SP7025, SP7031, LTC1006L, LTC1063L, LTC1036M, LTC1056L, SRX357, SRX211, SRX345, SRX370, LTC300B, LTC310, LTC355A, LTC759, LTC755, LTC750A, LTC752, LTC761, LTC856, LTC851, etc. manufactured by Dow Corning Toray Co., Ltd. However, the present invention is not limited to these.

[0051] Furthermore, a high release additive may be added to the silicone polymer not containing a fluorine substituent. Examples of such an additive include KS-3800 manufactured by Shin-Etsu Chemical Co., Ltd. and SD7292 and BY24-4980 manufactured by Dow Corning Toray Co., Ltd.

[0052] The silicone polymer not containing a fluorine substituent may be used alone, or two or more types having different reactive functional groups or different viscosities may be mixed and used. By mixing two or more types of silicone polymers that do not contain fluorine substituents, it is possible to adjust the curing reaction, adjust the viscosity of the coating liquid, and further increase the wettability and reactivity. In this case, it is possible to mix solventless silicones together, to mix solvent-type silicones together, or to mix solventless silicones and solvent-type silicones. The solvent-curable silicone and the solventless-curable silicone are as described above except that they do not contain a fluorine substituent, and the preferred viscosity ranges for each are also the same as those described above.

[0053] The content of the (E) silicone polymer not containing a fluorine substituent in the present release layer composition is not particularly limited as long as it is within a range that does not impair the effects of the present invention, but it is, for example, 0 to 99 parts by mass, preferably 0 to 80 parts by mass, and more preferably 0 to 40 parts by mass per 100 parts by mass of the present release layer composition.

[0054] (Other Ingredients) The release layer composition may contain other components as necessary in addition to the above components. For example, non-curable silicones other than the above (A) to (E), silicone rubbers, silicone resins, polyolefin resins, acrylic resins, urethane resins, epoxy resins, alkyd resins, cellulose resins, and copolymers of these resins modified by graft polymerization, etc.; various particles such as silica particles, alumina particles, silicone rubber particles, silicone resin particles, and silicone rubber / resin composite particles; silane coupling agents, etc. can be mentioned. However, the present invention is not limited to these.

[0055] The release layer composition may contain additives, such as a light release agent, a heavy release agent, and an adhesion improver, as required. Specific examples of the light release agent, heavy release agent, and adhesion improver include KS-3800 and X-92-185 manufactured by Shin-Etsu Chemical Co., Ltd., and BY24-850, SD7292, BY24-4980, SP7297, BY24-808, and SD7200 manufactured by Dow Corning Toray Co., Ltd., but are not limited to these.

[0056] (Solids) The release layer composition may be diluted with a diluting solvent such as an organic solvent, as described later. The solid content concentration of the release layer composition is preferably 0.1% by mass to 100% by mass, more preferably 0.5% by mass or more, even more preferably 1.0% by mass or more, even more preferably 1.5% by mass or more, and more preferably 50% by mass or less, even more preferably 20% by mass or less, and even more preferably 10% by mass or less.

[0057] The solid content of the release layer composition preferably contains alkylvinyl polysiloxane and alkylhydrogen polysiloxane as described above. Among them, the preferred amount of alkylalkenyl polysiloxane containing alkenyl groups such as vinyl groups is 85.0 to 99.9 mass% based on the mass of the solid content, more preferably 90.0 mass% or more, even more preferably 92.0 mass% or more, more preferably 99.5 mass% or less, and even more preferably 99.0 mass% or less. Note that each polysiloxane in this paragraph includes those containing fluorine atoms.

[0058] <<Release film>> A release film according to one embodiment of the present invention includes a base film and a release layer on one or both sides of the base film.

[0059] <Release layer> The release layer in the release film is a layer formed by curing the release layer composition. In the distribution of fluorine atoms in the thickness direction of the release layer, fluorine is preferably unevenly distributed on the surface of the release layer. It is presumed that the uneven distribution of fluorine on the surface of the release layer in this manner can achieve excellent easy releasability and low migration properties that facilitate easy peeling from the silicone pressure-sensitive adhesive layer. In the present invention, as described above, by including two or more types of (A) crosslinkable fluorine-containing silicone polymers, it is possible to achieve uneven distribution of fluorine.

[0060] In addition, by carrying out the "pre-treatment (pre-reaction)" described later, fluorine can be distributed unevenly on the surface compared to the case where the pre-reaction is not carried out. With this configuration, it is possible to improve the light release property, low migration property, and adhesion to the substrate compared to the case where the pre-reaction is not carried out. Although the detailed mechanism is not clear, the crosslinkable fluorine silicone polymer reacts in the liquid and the molecular weight increases by being "pre-treated". Among the two (or more) types of crosslinkable fluorine silicone polymer, the polymer with a high fluorine content (fewer reactive substituents) is particularly likely to be unevenly distributed on the surface, resulting in light release property. Accordingly, the polymer with a low fluorine content (more reactive substituents) is unevenly distributed on the substrate side, but since the fluorine content is low (more reactive substituents), it is thought that a release layer with excellent curability and adhesion to the substrate can be obtained. In order to make fluorine unevenly distributed on the surface of the release layer in this way, it is preferable to carry out the "pre-treatment" described below more thoroughly, although the present invention is not limited to such a method.

[0061] The fluorine atom content in the release layer is preferably 3000 mol ppm or more, more preferably 10,000 mol ppm or more, and even more preferably 50,000 mol ppm or more, from the viewpoint of obtaining stable and preferable easy peelability for silicone pressure sensitive adhesive.On the other hand, the upper limit is not particularly limited, but is preferably 900,000 mol ppm or less, more preferably 800,000 mol ppm or less, and even more preferably 700,000 mol ppm or less.

[0062] The fluorine atom ratio on the surface of the release layer is preferably 20% or more and 60% or less. The fluorine atom ratio within the above range makes it easier to achieve both easy releasability and low migration. The fluorine atom ratio is more preferably 30% or more and 50% or less, and even more preferably 36% or more and 43% or less. The fluorine atom ratio can be measured by using GC-IB (gas cluster ion beam) in XPS (X-ray photoelectron spectroscopy) to measure carbon (C), oxygen (O), silicon (Si), and fluorine (F) atoms and determining the ratio of fluorine atoms.

[0063] In addition, the release layer preferably has a ratio (t1[75%] / t2[50%]) of 1 to 24%. The ratio (t1[75%] / t2[50%]) is measured by the following method. That is, using GC-IB for XPS, the concentration distribution (ratio) of carbon (C), oxygen (O), silicon (Si) and fluorine (F) atoms in the thickness direction of the release layer of the sample film is measured under a constant sputtering rate (sputtering condition setting). In the obtained fluorine atom concentration distribution, the ratio (t1[75%] / t2[50%]) of the sputtering time required for the fluorine atom ratio to fall to 75% of the outermost surface (t1[75%]) to the time required for the fluorine atom ratio to fall to 50% of the outermost surface (t2[50%]) is calculated as a percentage (%), based on the fluorine atom ratio of the outermost surface (sputtering time 0).

[0064] The smaller the ratio (t1[75%] / t2[50%]), the more fluorine is distributed toward the surface side of the release layer. Therefore, when the ratio (t1[75%] / t2[50%]) is as low as 24% or less as described above, it becomes easier to achieve light releasability. From this perspective, the ratio (t1[75%] / t2[50%]) is more preferably 20% or less, even more preferably 18% or less, and even more preferably 15% or less. In addition, the larger the ratio (t1[75%] / t2[50%]), the more a certain amount of fluorine atoms are dispersed into the inside of the release layer, the more fluorine on the surface of the release layer is stably maintained, and the more the migration of the release agent component to the silicone adhesive layer can be prevented. From this viewpoint, the ratio (t1[75%] / t2[50%]) is preferably 1% or more as described above, more preferably 4% or more, even more preferably 7% or more, and particularly preferably 10% or more.

[0065] (Release layer thickness) The thickness of the release layer is not particularly limited. If the thickness of the release layer is thick, the influence of the substrate, for example the influence of the hardness of the substrate, tends to be less likely to be transmitted to the release surface of the release film, so it is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.10 μm or more. On the other hand, if the thickness of the release layer is set to a certain level or less, blocking can be prevented, and the deterioration of the coat appearance can be prevented, so it is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, more preferably 1 μm or less, and even more preferably 0.5 μm or less.

[0066] <Base film> The base film of the release film is not particularly limited in material as long as it has a film shape. For example, it may be made of paper, resin, metal, etc. Among these, it is preferable to use a resin from the viewpoint of mechanical strength and flexibility.

[0067] Examples of the resin substrate film (resin film) include films formed from polymers such as polyethylene, polypropylene, polyester, polystyrene, polycarbonate, polyethersulfone, polyamide, and polyimide in the form of a film. However, the film is not limited to these. In addition, as long as it can be made into a film, it may be a mixture of these materials (polymer blend) or a composite of the structural units (copolymer).

[0068] Among the above-mentioned films, polyester films are particularly preferred because they have excellent physical properties such as heat resistance, flatness, optical properties, and strength. The polyester film may be a single layer film or a multilayer film (laminate film) having two or more layers with different properties. The polyester film may be a non-stretched film (sheet) or a stretched film. Of these, a uniaxially or biaxially stretched film is preferred. Of these, a biaxially stretched film is more preferred from the viewpoints of balance of mechanical properties and flatness.

[0069] The polyester that is the main component resin of the polyester film may be either a homopolyester or a copolymer polyester. The term "main component resin" refers to the resin that has the largest mass proportion among the resins constituting the polyester film, and is expected to account for 50 mass% or more, 75 mass% or more, 90 mass% or more, or 100 mass% of the resins constituting the polyester film.

[0070] The homopolyester is preferably one obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid, and examples of the aliphatic glycol include ethylene glycol, diethylene glycol, 1,4-butanediol, and 1,4-cyclohexanedimethanol, but are not limited thereto. Representative examples of homopolyester include polyethylene terephthalate (PET) and polybutylene terephthalate (PBT).

[0071] On the other hand, when the polyester is a copolymer polyester, it is preferable that the polyester is a copolymer containing 30 mol % or less of a third component. Examples of the dicarboxylic acid component of the copolymer polyester include one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, etc., and examples of the glycol component include one or more of ethylene glycol, diethylene glycol, propylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, etc., but are not limited to these.

[0072] Among these, the main component resin of the base film is preferably polyethylene terephthalate, in which 60 mol % or more, preferably 80 mol % or more, is ethylene terephthalate unit.

[0073] The base film may contain particles for the main purpose of imparting easy slippage and preventing scratches in each process. When particles are contained, the type of particles contained is not particularly limited as long as they are particles that can impart easy slippage, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenolic resin, epoxy resin, and benzoguanamine resin. However, the present invention is not limited to these. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester production process may also be used.

[0074] On the other hand, the shape of the particles to be used is not particularly limited, and any of spherical, blocky, rod-like, flat, etc. may be used. In addition, there is no particular limit to the hardness, specific gravity, color, etc. Two or more kinds of these particles may be used in combination as necessary.

[0075] The average particle size of the particles is preferably 5 μm or less, more preferably in the range of 0.1 μm to 3 μm. By using particles with an average particle size in the above range, a suitable surface roughness can be imparted to the film, and good slipperiness and smoothness can be ensured. The average particle size of the particles can be measured as follows. The average particle size of the particles as the raw material can be measured as the average particle size (D50) determined from the volume-based particle size distribution measured by a dynamic light scattering method or the like. The average particle size of the particles contained in the base film can be determined by observing the surface or cross section of the base film using an optical microscope or a scanning electron microscope (SEM), measuring the diameters of 10 or more particles, and calculating the average value. In this case, if the cross section is elliptical, the average value of the longest and shortest diameters can be measured as the diameter of each particle.

[0076] Furthermore, the particle content in the base film is preferably 5% by mass or less, more preferably 0.0003% by mass or more and 3% by mass or less. By making the particle content equal to or more than these lower limits, slipperiness can be ensured. Furthermore, when there are no particles or when there are only a few particles, the film becomes highly transparent and is a good film. However, since slipperiness may be insufficient, it may be necessary to take measures such as adding particles to the coating layer to improve slipperiness.

[0077] In addition, the multilayer film preferably has a surface layer constituting the surface of the base film and a core layer, and the surface layer preferably contains the above-mentioned particles. When the surface layer contains the above-mentioned particles, the content of the particles in the surface layer preferably falls within the above-mentioned range. The multilayer film may have a two-layer structure of a surface layer and a core layer, or a three-layer structure of a surface layer, a core layer, and a surface layer, or may have a four-layer structure in which the core layer is made of two or more layers.

[0078] <Examples of release film composition> The release film may have a configuration in which a release layer is provided on one or both sides of a base film. As described below, the base film and the release layer may be laminated directly to each other on one or both sides of the release film, or may be laminated via another layer.

[0079] Examples of the "other layer" include an anchor coat layer for increasing the adhesion between the base film and the release layer, an oligomer sealing layer for sealing the exudation (bleed, plate-out) of a compound or oligomer onto the film surface, and an antistatic layer having antistatic properties, but are not limited to these.

[0080] Specific examples of the release film include base film / release layer, base film / anchor coat layer / release layer, base film / antistatic layer / release layer, base film / oligomer sealing layer / release layer, antistatic layer / base film / antistatic layer / release layer, oligomer sealing layer / base film / oligomer sealing layer / release layer, base film / antistatic layer / oligomer sealing layer / release layer, release layer / base film / release layer, release layer / anchor coat layer / base film / anchor coat layer / release layer, release layer / antistatic layer / base film / antistatic layer / release layer, release layer / oligomer sealing layer / base film / oligomer sealing layer / release layer, release layer / oligomer sealing layer / antistatic layer / base film / oligomer sealing layer / release layer, release layer / oligomer sealing layer / antistatic layer / base film / oligomer sealing layer / release layer, release layer / oligomer sealing layer / antistatic layer / base film / antistatic layer / oligomer sealing layer / release layer, etc. However, the present invention is not limited to these.

[0081] (Anchor coat layer) Examples of the anchor coat layer include those containing polymer materials such as polyethylene, polypropylene, styrene copolymers, polyester, polyurethane, polyvinyl alcohol, polyethyleneimine, polyacrylate, polymethacrylate, and modified products thereof, but are not limited to these.

[0082] (Oligomer sealing layer) The oligomer sealing layer may contain a hydrolyzable alkoxy silicate and / or a polycondensate thereof. The hydrolyzable alkoxy silicate may be a compound having a structure represented by the following general formula (3): 1 represents a hydrocarbon group having 1 to 10 carbon atoms.

[0083] Si(OR 1 )4(3)

[0084] In formula (3), R 1 represents a hydrocarbon group having 1 to 10 carbon atoms.

[0085] The oligomer sealing layer may further contain inorganic particles, and specific examples of inorganic particles include, but are not limited to, silica, alumina, kaolin, calcium carbonate, titanium oxide, barium salts, and the like. The oligomer sealing layer may also contain, but is not limited to, an antifoaming agent, a coating improver, a thickener, an organic lubricant, an organic polymer particle, an antioxidant, an ultraviolet absorber, a foaming agent, a dye, and the like.

[0086] (Antistatic layer) From the viewpoint of imparting antistatic properties, the antistatic layer preferably contains a conductive polymer and a binder polymer. The coating liquid may contain other components as long as the gist of the present invention is not impaired.

[0087] Specifically, the conductive polymer preferably contains a polythiophene having a repeating unit represented by the following formula (4) and a derivative (I) thereof.

[0088] [ka]

[0089] In the above formula (4), R1 and R2 each independently represent a hydrogen atom, an aliphatic hydrocarbon group having 1 to 12 carbon atoms, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a cyclohexylene group, a benzene group, etc., but are not limited to these.

[0090] The above-mentioned anchor coat layer, antistatic layer, oligomer sealing layer, and other layers can be formed by either an in-line coating method in which they are formed simultaneously with the production of a film-like substrate, or an off-line coating method in which they are formed in a separate process on an already-produced substrate film. A specific example of an in-line coating method is a method in which coating is performed at any stage from melt extrusion of polyester to biaxial stretching, heat setting, and winding up. Usually, this method is performed by coating either a substantially amorphous unstretched sheet obtained by melting and quenching, a uniaxially stretched film that has been subsequently stretched in the longitudinal direction (machine direction), or a biaxially stretched film before heat setting.

[0091] <<Release layer composition and method for producing release film>> Next, an example of a method for producing the release layer composition and the release film will be described. In one preferred example of a method for producing the release layer composition of the present invention, at least one type of (A) crosslinkable fluorine silicone polymer is crosslinked in advance in a blend liquid, and then at least another (A) crosslinkable fluorine silicone polymer is mixed therein to prepare the composition. More specifically, a method includes mixing (A) a crosslinkable fluorine silicone polymer (first (A) component), (B) a silicone crosslinker, and (C) a curing catalyst, followed by a "pretreatment" of stirring and / or allowing to stand, and then mixing the pretreatment composition obtained in the pretreatment with (A) a crosslinkable fluorine silicone polymer (second (A) component) different from the first (A) component to prepare a release layer composition. The resulting release layer composition may then be applied to at least one side of a substrate film to produce a release film. The process of mixing components (A), (B), and (C) prior to pre-treatment is also referred to as the pre-stage process, and the process of mixing another (A) cross-linkable fluorine-silicone polymer (second (A) component) after pre-treatment is also referred to as the post-stage process.

[0092] Generally, in a release film, measures to reduce the amount of crosslinkable fluorine silicone polymer (fluorinated silicone) used can be, for example, reducing the content ratio of fluorinated silicone in the release layer, reducing the film thickness of the release layer, etc. However, the former method impairs the original purpose of light releasability, and the latter method has problems such as not being able to form a uniform release layer or reducing the stability of the release force. Meanwhile, in the present invention, by using a combination of at least two or more different crosslinkable fluorine-containing silicone polymers (A) as described above, it is possible to maintain light releasability. However, when a solution of two different (A) cross-linkable fluorosilicone polymers is mixed and applied onto a film and dried, the (B) silicone cross-linking agent and (C) curing catalyst may not be dispersed uniformly enough in the film, and cross-linking may not progress sufficiently, making it difficult to obtain a release layer in an excellent cured state or to obtain the desired light releasability. Therefore, in the present invention, in forming the release layer, first, a "pretreatment" is carried out, and then, by mixing another (A) crosslinkable fluorine silicone polymer to prepare a release layer composition, the (B) silicone crosslinking agent and (C) curing catalyst, etc. can be uniformly dispersed, and a coating film that is easier to peel off from the silicone pressure-sensitive adhesive (light peelability) can be formed. Furthermore, by carrying out such a pretreatment, even when the (B1) non-fluorine silicone crosslinking agent, which tends to be difficult to disperse when used in combination with the (A) crosslinkable fluorine silicone polymer, is used as the (B) silicone crosslinking agent, it is possible to sufficiently uniformly disperse it.

[0093] After mixing (A) the crosslinkable fluorine silicone polymer, (B) the silicone crosslinking agent, and (C) the curing catalyst, a "pre-treatment" is carried out by stirring and / or leaving the mixture to stand for a short period of time, allowing the crosslinking reaction (also referred to as "pre-crosslinking") to proceed in the mixed liquid at room temperature. In this case, the "agitation and / or standing" or "pretreatment" may be any method that involves the passage of time to allow the crosslinking reaction to proceed, such as shaking. The pretreatment time, such as agitation and / or standing, is preferably 10 seconds or more, more preferably 1 minute or more, and particularly preferably 3 minutes or more, more preferably 5 minutes or more, and particularly preferably 15 minutes or more. There is no particular upper limit to the pretreatment time. From the viewpoint of solvent evaporation and workability, it is preferably within 1 week, more preferably within 3 days, and particularly preferably within 1 day. The temperature of the mixed liquid in the pretreatment is not particularly limited, but is, for example, about 5 to 50°C, and preferably about 10 to 30°C. With (A) crosslinkable fluorine silicone polymer, pre-crosslinking proceeds appropriately in the pretreatment, so that after application, the fluorine substituents of component (A) tend to be unevenly distributed on the surface of the release layer, ensuring light releasability. In addition, crosslinking proceeds easily enough, so that the fluorine substituents of component (A) unevenly distributed on the surface are stably maintained, making it easier to ensure low migration. The pretreatment may be performed in a state where the pretreatment composition is diluted with an organic solvent as long as the pre-crosslinking proceeds, or may not be diluted with an organic solvent. The solid content of the pretreatment composition is, for example, 4 to 100 mass%, preferably 5 to 50 mass%, and more preferably about 7 to 20 mass%. Increasing the solid content makes it easier to proceed with the pre-crosslinking.

[0094] As described above, it is preferable to use the (B) silicone crosslinking agent mixed in the previous step as the (B1) non-fluorinated silicone crosslinking agent.In this case, the (B) silicone crosslinking agent used in the previous step may be the (B1) non-fluorinated silicone crosslinking agent alone, or the (B1) non-fluorinated silicone crosslinking agent and the (B2) fluorinated silicone crosslinking agent in combination.In addition, the first (A) component used in the previous step may be a solvent-curable silicone. Furthermore, in the previous step, components other than the components (A), (B), and (C) may be mixed, for example, a reaction inhibitor (D) or compounds listed under other components may be appropriately mixed in. Furthermore, the mixing of each component in the previous step may be performed by stirring or the like until each component is dissolved or substantially uniformly dispersed in the composition.

[0095] In the latter step, as described above, another (A) cross-linkable fluorine-containing silicone polymer (second component (A)) is mixed with the pre-treatment composition. As described above, the second (A) component is a crosslinkable fluorine silicone polymer (A) that differs from the first (A) component in at least one of the ratio of fluorine substituents, the structure of the fluorine substituents, and the viscosity or weight average molecular weight. The mixing ratio of the first (A) component and the second (A) component may be as described above. The second (A) component to be mixed in the latter step is not particularly limited, but it is preferable to use a solventless curable silicone.

[0096] In the latter step, in addition to the crosslinkable fluorine silicone polymer (A), components other than component (A) may be mixed into the pre-treatment composition, for example, a silicone crosslinking agent (B), a curing catalyst (C), etc. The silicone crosslinking agent (B) mixed in the latter step may be a non-fluorinated silicone crosslinking agent (B1) alone or a fluorinated silicone crosslinking agent (B2) alone, or a combination of a non-fluorinated silicone crosslinking agent (B1) and a fluorinated silicone crosslinking agent (B2). The amount of silicone crosslinking agent (B) mixed in the latter step is not particularly limited, but the ratio to the amount of silicone crosslinking agent (B) mixed in the former step is, although not particularly limited, for example, 0.1 to 10, preferably 0.25 to 7, and more preferably 0.5 to 5, on a mass basis.

[0097] In addition, in this method, after a predetermined pre-crosslinking time has elapsed, the reaction regulator (D) such as the above-mentioned acetylene alcohol may be added or added. If the crosslinking reaction proceeds too far, depending on the type of material, the liquid may become cloudy or gel, but the crosslinking reaction can be appropriately suppressed by adding or adding a reaction regulator. The (D) reaction inhibitor may be added in advance to another (A) crosslinkable fluorosilicone polymer (second (A) component) that is mixed into the pretreatment composition.

[0098] It is preferable to mix the pretreatment composition obtained in the above pretreatment with another crosslinkable fluorine-containing silicone polymer (A) and then dilute with a solvent as necessary to prepare a release layer composition. The solvent for dilution may be a polar solvent or a non-polar solvent, and two or more of the above solvents may be mixed together. Examples of the polar solvent include alcohols such as ethanol and (iso)propyl alcohol, esters such as methyl acetate, ethyl acetate, (iso)propyl acetate, (iso)butyl acetate, (iso)pentyl acetate, ethyl lactate, and ethyl benzoate, ketones such as methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, diacetone alcohol, and diisobutyl ketone, glycols such as ethylene glycol, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether acetate, and propylene glycol monomethyl ether, N-methyl-2-pyrrolidone, N,N-dimethylformamide, tetrahydrofuran, and acetonitrile, but are not limited thereto. Examples of the non-polar solvent include aromatic hydrocarbons such as benzene, toluene, and xylene, aliphatic hydrocarbons such as hexane, heptane, and octane, hydrocarbons having a branched structure such as isohexane, isooctane, and isononane, alicyclic hydrocarbons such as cyclohexane, cycloheptane, and cyclooctane, ethers such as diisopropyl ether, and dioxane. Fluorine solvents may be used as the non-polar solvent. Examples of the fluorine solvent include hydrofluoroethers, metaxylene hexafluoride, and tridecafluorooctane. In addition, commercially available products such as "FS Thinner" (manufactured by Shin-Etsu Chemical Co., Ltd.) may be used as the fluorine solvent. However, the present invention is not limited to these.

[0099] As a method for applying the release layer composition to the substrate film, for example, a coating technique such as that shown in "Coating Method" (by Yuji Harazaki, Maki Shoten, published in 1979) can be used. For example, examples of coating heads include air doctor coaters, blade coaters, rod coaters, knife coaters, squeeze coaters, impregnation coaters, reverse roll coaters, transfer roll coaters, gravure coaters, kiss roll coaters, cast coaters, spray coaters, curtain coaters, calendar coaters, extrusion coaters, etc. However, they are not limited to these.

[0100] The method for preparing the release layer composition is not limited to the above-mentioned method, and may be other methods, for example, the above-mentioned pretreatment may not be performed. That is, after mixing the first (A) component, the (B) component, and the (C) component, another (A) crosslinkable fluorine silicone polymer (second (A) component) may be mixed into the obtained composition immediately to prepare the release layer composition. The release layer composition may be prepared by any other method as long as the components constituting the composition are mixed together, and the components may be mixed in an order different from that described above. Furthermore, when the release layer composition contains the above-mentioned component (E) and other components, these components may be added at any stage.

[0101] (Method of forming other layers) As described above, the release film can be formed by forming "other layers" such as an anchor coat layer, an antistatic layer, an oligomer sealing layer, etc., as necessary on one or both sides of a base film, and then applying and curing a release layer composition. When forming "other layers" in this manner, "other layers" such as an anchor coat layer, an antistatic layer, an oligomer sealing layer, etc. are formed, as necessary, on at least one side of the base film unwound from a roll, and then a release layer composition is applied and cured to form a release layer.

[0102] <Release film properties> The release film may have the following physical properties:

[0103] (Normal peel strength) The normal peel strength of the release layer is preferably 900 mN / cm or less, more preferably 800 mN / cm or less, even more preferably 500 mN / cm or less, even more preferably 400 mN / cm or less, and even more preferably 200 mN / cm or less. The lower the normal peel strength, the less force is required to peel off the silicone adhesive, and the less defects such as peel failure and deformation of the adhesive layer in the production process can be suppressed. In addition, by using a release film with excellent light peeling properties, it is possible to prevent the phenomenon that the release film on the unintended side is peeled off in a double-sided adhesive tape having a release film on both sides of the adhesive sheet. On the other hand, there is no particular restriction on the lower limit, but in terms of long-term storage of a laminate in which a release film and a pressure-sensitive adhesive are laminated, the lower limit is preferably 1 mN / cm or more. The normal peel strength can be evaluated by the method described below.

[0104] (Residual adhesive strength) The residual adhesive strength of the release layer is, for example, 3300 mN / cm or more, preferably 4000 mN / cm or more, more preferably 4200 mN / cm or more, and even more preferably 4400 mN / cm or more. By satisfying the above range, transfer of the components of the release layer from the surface to the surface of the opposing adherend to be bonded is reduced. Residual adhesive strength is an index for checking the transfer of the release agent, and is usually the value measured by applying an adhesive tape to a release agent-coated surface and then peeling it off (see JIS Z 0109:2015). In the present application, the residual adhesive strength is evaluated by the method described below.

[0105] <<Film laminate>> The release film (hereinafter, occasionally referred to as "the release film of the present invention") can be used in various film laminates. An example of a film laminate according to an embodiment of the present invention includes a release film of the present invention, a silicone pressure-sensitive adhesive layer, and a laminate film having a functional layer, and the release film of the present invention and the laminate film having the functional layer are bonded together via the silicone pressure-sensitive adhesive layer. In each film laminate, the release film of the present invention is disposed at a position where the release layer contacts the silicone pressure-sensitive adhesive layer.

[0106] <Laminated film (1)> The "laminated film having a functional layer" may be, for example, a laminated film having a base film and a crosslinked resin layer, i.e., a layer having a structure formed by crosslinking a resin, on at least one side of the base film (referred to as "laminated film (1)"). The base film is the same as that explained for the release layer above. In the following explanation, the base film of the laminated film (1) may be referred to as the base film (1).

[0107] In this case, the crosslinked resin layer may be, for example, a crosslinked resin layer composition containing a conductive polymer and a binder polymer, and optionally a crosslinking agent and particles. Such a crosslinked resin layer may be provided, for example, on the surface of the base film (1) opposite to the surface that is bonded to the silicone adhesive layer.

[0108] (Conductive Polymer) The conductive polymer preferably contains a composition comprising a polythiophene compound and a polyanion.

[0109] The polyanion refers to an "acidic polymer in a free acid state", and is preferably a polymeric carboxylic acid, or a polymeric sulfonic acid, polyvinyl sulfonic acid, or the like. Specific examples of polymeric carboxylic acids include polyacrylic acid, polymethacrylic acid, and polymaleic acid. Specific examples of polymeric sulfonic acids include polystyrene sulfonic acid. Among them, polystyrene sulfonic acid is most preferable in terms of electrical conductivity. In addition, the free acid may be in the form of a salt in which a part of the free acid is neutralized. By using these polyanions during polymerization, it is easy to disperse or make aqueous-soluble polythiophene-based compounds, which are originally insoluble in water, and it is considered that the function as an acid also functions as a doping agent for polythiophene-based compounds.

[0110] In addition, the polymeric carboxylic acid or polymeric sulfonic acid can be used in a form copolymerized with other copolymerizable monomers, such as acrylic acid esters, methacrylic acid esters, styrene, etc. The molecular weight of the polymeric carboxylic acid or polymeric sulfonic acid used as the polyanion is not particularly limited, but in terms of the stability and conductivity of the coating agent, the mass average molecular weight is preferably 1000 to 1000000, more preferably 5000 to 150000. It may contain alkali salts such as lithium salts and sodium salts, ammonium salts, etc., as long as the characteristics of the present invention are not impaired. In the case of neutralized salts, it has been found that polystyrene sulfonic acid and ammonium salts, which function as very strong acids, shift the equilibrium to the acidic side due to the progress of the equilibrium reaction after neutralization, and this is thought to act as a dopant.

[0111] Examples of the polythiophene-based compound include polythiophene or its derivatives. The polythiophene or its derivatives are as described above. It is preferable that the polyanion is present in excess of the polythiophene-based compound in terms of electrical conductivity in terms of solid content mass ratio, and the polyanion is preferably 1 part by mass to 5 parts by mass, more preferably 1 part by mass to 3 parts by mass, per part by mass of the polythiophene-based compound. Regarding the composition consisting of the above polythiophene-based compound and polyanion, for example, there are examples described in JP-A-6-295016, JP-A-7-292081, JP-A-1-313521, JP-A-2000-6324, European Patent EP602731, US Patent US5391472, etc., but methods other than these may also be used. As an example, 3,4-ethylenedioxythiophene is obtained using an alkali metal salt of 3,4-dihydroxythiophene-2,5-dicarboxy ester as a starting material, and then potassium peroxodisulfate, iron sulfate, and the previously obtained 3,4-ethylenedioxythiophene are introduced into an aqueous solution of polystyrene sulfonic acid and reacted to obtain a composition in which a polythiophene compound such as poly(3,4-ethylenedioxythiophene) is complexed with a polyanion such as polystyrene sulfonic acid. For example, there is an example described in "Latest Trends in Conductive Polymer Technology" (published by Toray Research Center, Inc., first printing June 1, 1999).

[0112] (Binder polymer) The binder polymer constituting the crosslinked resin layer composition is defined as a polymer compound having a number average molecular weight (Mn) of 1000 or more as measured by gel permeation chromatography (GPC) in accordance with the Polymer Compound Safety Evaluation Flow Scheme (November 1985, sponsored by the Chemical Substances Council), and having film-forming properties.

[0113] The binder polymer constituting the crosslinked resin layer composition may be a thermosetting resin or a thermoplastic resin as long as it is compatible with or can be mixed and dispersed in the ionic polymer. For example, polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyimides such as polyimide and polyamideimide; polyamides such as polyamide 6, polyamide 6,6, polyamide 12, and polyamide 11; fluororesins such as polyvinylidene fluoride, polyvinyl fluoride, polytetrafluoroethylene, ethylene tetrafluoroethylene copolymer, and polychlorotrifluoroethylene; vinyl resins such as polyvinyl alcohol, polyvinyl ether, polyvinyl butyral, polyvinyl acetate, and polyvinyl chloride; epoxy resins; oxetane resins; xylene resins; aramid resins; polyimide silicones; polyurethanes; polyureas; melamine resins; phenolic resins; polyethers; acrylic resins, and copolymers thereof. These may be used alone or in combination of two or more. However, the present invention is not limited to these.

[0114] The binder polymer may be dissolved in an organic solvent as a raw material, or may be dissolved in an aqueous solution by adding a functional group such as a hydroxyl group, a sulfo group, or a carboxy group, or may be dispersed in water by using a surfactant in combination. In addition, the binder polymer may be used in combination with a crosslinking agent, a curing agent such as a polymerization initiator, a polymerization accelerator, a solvent, a viscosity modifier, etc., as necessary.

[0115] Among the binder polymers, from the viewpoint of adhesion to the release layer, it is preferable to use at least one selected from polyester resins, acrylic resins, urethane resins, and vinyl resins.

[0116] The content of the binder polymer in the crosslinked resin layer composition is preferably 5 to 90% by mass, more preferably 10 to 70% by mass, and further preferably 10 to 60% by mass, in terms of solid content mass ratio. When the content of the binder polymer is within the above range, the strength of the obtained crosslinked resin layer and the adhesion to the release layer can be sufficiently obtained.

[0117] (Crosslinking agent) The crosslinked resin layer composition may contain a crosslinking agent, if necessary. The crosslinking agent can improve the cohesiveness, surface hardness, scratch resistance, solvent resistance, water resistance, etc. of the crosslinked resin layer mainly by crosslinking reactions with functional groups contained in other resins or compounds, or by self-crosslinking.

[0118] Any type of crosslinking agent can be used. For example, melamine compounds, guanamine-based, alkylamide-based, and polyamide-based compounds, glyoxal-based, carbodiimide compounds, epoxy compounds, oxazoline compounds, aziridine compounds, isocyanate compounds, silane coupling agents, dialcohol aluminate-based coupling agents, dialdehyde compounds, zircoaluminate-based coupling agents, peroxides, heat- or light-reactive vinyl compounds, photosensitive resins, and the like are preferably used. Among them, from the viewpoint of synergistically obtaining good adhesion to the release layer, it is preferable to use melamine compounds, epoxy compound crosslinking agents, and silane coupling agents. These crosslinking agents also include polymer-type crosslinking reactive compounds having reactive groups on other polymer skeletons, and in the present invention, these crosslinking agents may be used alone or in combination of two or more.

[0119] The content of the crosslinking agent in the crosslinked resin layer composition is preferably 1 to 90% by mass, more preferably 3 to 50% by mass, and further preferably 5% to 40% by mass, in terms of solid content mass ratio. If the ratio of the crosslinking agent is within the above range, sufficient adhesion to the release layer can be obtained due to the synergistic effect with the binder polymer.

[0120] (particle) For the purpose of improving the adhesion and slippage of the crosslinked resin layer, the crosslinked resin layer may contain particles. There is no particular restriction on the average particle size of the particles. For example, when used for optical purposes, from the viewpoint of film transparency, the average particle size is preferably 1.0 μm or less, more preferably 0.5 μm or less, and even more preferably 0.2 μm or less. Also, from the viewpoint of improving the adhesion and slip properties of the crosslinked resin layer, the average particle size is preferably 0.01 μm or more. Specific examples of particles include inactive inorganic particles such as silica, alumina, calcium carbonate, and titanium dioxide; fine particles obtained from polystyrene resins, polyacrylic resins, and polyvinyl resins; and organic particles such as crosslinked particles of these resins.

[0121] The average particle size of the particles can be measured as follows. The average particle size of the particles as the raw material can be measured as the average particle size (D50) determined from the volume-based particle size distribution measured by a dynamic light scattering method or the like. The average particle size of the particles contained in the crosslinked resin layer can be determined by observing the surface or cross section of the crosslinked resin layer using an optical microscope or a scanning electron microscope (SEM), measuring the diameters of 10 or more particles, and calculating the average value. In this case, if the cross section is elliptical, the average value of the longest diameter and the shortest diameter can be measured as the diameter of each particle.

[0122] In another embodiment, the crosslinked resin layer may be an easy-adhesion layer formed from a composition containing a binder polymer, a crosslinking agent, a silane coupling agent, particles, etc. The easy-adhesion layer is an easy-adhesion layer for the silicone adhesive layer, and may be provided on the surface of the substrate film (1) that is to be adhered to the silicone adhesive layer. The binder polymer, the crosslinking agent, and the particles are as described above.

[0123] (others) The crosslinked resin layer may contain, as necessary, a surfactant, an antifoaming agent, a coatability improving agent, a release agent, a thickener, an organic lubricant, an antistatic agent, a conductive agent, an ultraviolet ray or other light absorber, an antioxidant, a foaming agent, a dye, a pigment, and the like.

[0124] The components in the crosslinked resin layer can be analyzed by, for example, TOF-SIMS, ESCA, fluorescent X-ray analysis, or the like. In addition, in the laminate film (1), a crosslinked resin layer formed from a crosslinked resin layer composition containing a conductive polymer and a binder polymer may be provided on one surface of the base film (1), and the above-mentioned easy-adhesion layer may be provided on the other surface.

[0125] (Method of forming crosslinked resin layer) The crosslinked resin layer may be formed by in-line coating, which treats the film surface on the production line of the base film (1), such as during the stretching process of a stretched film such as a polyester film, or by off-line coating, which applies the coating outside the production line onto the base film (1) that has already been produced. In-line coating is preferably used because it can be applied simultaneously with film formation, making production inexpensive, and the thickness of the crosslinked resin layer can be changed by changing the stretching ratio.

[0126] Although the in-line coating is not limited to the following, for example, in the case of sequential biaxial stretching, a coating treatment can be carried out especially before transverse stretching after the completion of longitudinal stretching. When a crosslinked resin layer is provided on a base film (1) such as a polyester film by in-line coating, coating can be performed simultaneously with film formation, and the crosslinked resin layer can be treated at a high temperature, so that a polyester film suitable as the base film (1) can be produced.

[0127] When the crosslinked resin layer is provided by in-line coating, it is preferable to coat a coating liquid as an aqueous solution or aqueous dispersion of the crosslinked resin layer composition containing the above-mentioned series of compounds on a substrate film (1) such as a polyester film. In addition, the coating liquid may contain a small amount of an organic solvent for the purpose of improving dispersibility in water, improving film-forming properties, etc., within a range that does not impair the gist of the present invention. One or more organic solvents can be used in combination.

[0128] The content of the organic solvent in the coating liquid is preferably 10% by mass or less, more preferably 5% by mass or less.Specific examples of the organic solvent include aliphatic or alicyclic alcohols such as n-butyl alcohol, n-propyl alcohol, isopropyl alcohol, ethyl alcohol, and methyl alcohol, glycols such as propylene glycol, ethylene glycol, and diethylene glycol, glycol derivatives such as n-butyl cellosolve, ethyl cellosolve, methyl cellosolve, and propylene glycol monomethyl ether, ethers such as dioxane and tetrahydrofuran, esters such as ethyl acetate and amyl acetate, ketones such as methyl ethyl ketone and acetone, and amides such as N-methylpyrrolidone.

[0129] Regardless of whether off-line coating or in-line coating is used, in order to crosslink the crosslinked resin layer composition, a heat treatment and irradiation with active energy rays such as ultraviolet rays may be used in combination as necessary.

[0130] Examples of a method for forming the crosslinked resin layer include gravure coating, reverse roll coating, die coating, air doctor coating, blade coating, rod coating, bar coating, curtain coating, knife coating, transfer roll coating, squeeze coating, curtain coating, impregnation coating, kiss coating, spray coating, calendar coating, and extrusion coating.

[0131] (Thickness of cross-linked resin layer) From the viewpoint of exhibiting various functionalities when viewed as a final coating, the thickness of the crosslinked resin layer is preferably 0.01 μm to 3 μm, more preferably 0.02 μm or more, even more preferably 0.03 μm or more, and more preferably 1 μm or less, even more preferably 0.3 μm or less. The coating amount of the coating solution containing the crosslinked resin layer composition is usually 0.01 to 3 g / m in terms of solid content. 2 , preferably 0.01 to 1 g / m 2 , and more preferably 0.01 to 0.3 g / m 20.01g / m 2 If the thickness is 3 g / m or more, sufficient performance can be obtained in terms of antistatic performance or adhesion to the silicone adhesive layer (i.e., easy adhesion performance). 2 If it is equal to or less than this, the crosslinked resin layer has good appearance and transparency, and there is no risk of film blocking or reduced productivity due to a decrease in line speed. In the present invention, the coating amount can be calculated from the liquid mass per coating time (before drying), the non-volatile content concentration of the coating liquid, the coating width, the stretching ratio, the line speed, and the like.

[0132] <Laminated film (2)> The "laminated film having a functional layer" may be, for example, a release film (referred to as "laminated film (2)") having a base film and another release layer provided on one side of the base film. The other release layer may be provided on the silicone adhesive layer side, and the laminated film (2) is adhered to the silicone adhesive layer via the other release layer. The other release layer may be a release layer other than the above-mentioned release layer, and may be, for example, a release layer formed from a silicone release agent. The base film is the same as that described for the release layer above. In the following description, the base film of the laminated film (2) may be referred to as the base film (2).

[0133] An example of the other release layer is one that is configured to sequentially include a first layer formed from a silicone composition containing (E) a silicone polymer without a fluorine substituent as a main component, and a second layer containing a component with a fluorine substituent. In this configuration, the second layer is preferably a layer that contacts the silicone pressure-sensitive adhesive layer. An example of the second layer is a layer formed from a silicone composition containing (A) a crosslinkable fluorine silicone polymer as a main component.

[0134] Another example of the "other release layer" is a layer formed from a silicone composition containing a crosslinkable fluorine-containing silicone polymer as a main component (A).

[0135] Furthermore, another example of the "other release layer" is (E) a layer formed from a silicone composition containing as a main component a silicone polymer that does not contain a fluorine substituent.

[0136] The above-mentioned "main component" means the component that occupies the largest mass proportion among the constituent components. In addition, (A) the cross-linkable fluorine silicone polymer and (E) the silicone polymer not containing a fluorine substituent are as described above, but in other release layers, it is not necessary to use two or more types of (A) the cross-linkable fluorine silicone polymer. In addition, in the laminate film (2), another release layer may be provided on one surface of the base film (2), and a crosslinked resin layer formed from a crosslinked resin layer composition containing a conductive polymer and a binder polymer may be provided on the other surface.

[0137] <Resin film> Another example of a film laminate according to an embodiment of the present invention includes a film laminate including the release film of the present invention described above, a silicone pressure-sensitive adhesive layer, and a resin film, and the resin film is directly bonded to the release film of the present invention via the silicone pressure-sensitive adhesive layer. Here, "directly bonded" means that the resin film itself is adhered to the silicone pressure-sensitive adhesive layer without any other layer such as the crosslinked resin layer. As the resin film, a conventionally known film such as a polyester film, a polyimide film, or a polyolefin film can be used depending on the purpose.

[0138] <Applications of film laminates> The film laminate is preferably used for bonding on-vehicle members, since a silicone pressure-sensitive adhesive having good durability and transparency can be used therefor.

[0139] <How to use the release film and film laminate> Since the release film of the present invention has excellent releasability with respect to silicone pressure-sensitive adhesives, it can be used as a light release film for silicone pressure-sensitive adhesives as follows. That is, the release film of the present invention (referred to as "light release film") can be used in a film laminate comprising the light release film, a silicone pressure-sensitive adhesive layer, and a heavy release film, the light release film being laminated on one side of the silicone pressure-sensitive adhesive layer, and the heavy release film being laminated on the other side of the silicone pressure-sensitive adhesive layer, the heavy release film having a higher peel strength (for example, the above-mentioned normal peel strength) than the light release film. In this film laminate, after peeling off the light release film, the exposed surface of the silicone pressure-sensitive adhesive layer is attached to an "adherend", and the silicone pressure-sensitive adhesive layer is cured as necessary, and then the heavy release film is peeled off. The film laminate having the above-mentioned laminated film (2) can be suitably used in such a method of use. However, the method of use is not limited to this.

[0140] The silicone pressure-sensitive adhesive layer of each film laminate can be attached to an adherend, for example, various types of process paper, insert paper, or optical components. The optical components can be polarizing plates, touch sensors, or the like. In addition, the silicone pressure-sensitive adhesive itself has heat resistance, cold resistance, weather resistance, and high transparency, so it can be used for in-vehicle applications such as touch panels mounted on automobiles, and therefore the adherend is preferably an in-vehicle optical component.

[0141] (Silicone adhesive) Each of the silicone pressure-sensitive adhesive layers is made of a silicone pressure-sensitive adhesive. The silicone pressure-sensitive adhesive may be a pressure-sensitive adhesive containing silicone as a main component resin. The "main component resin" refers to the resin that has the largest content (mass) among the resins that make up the pressure-sensitive adhesive. Examples of the silicone adhesive include addition reaction type, peroxide curing type, and condensation reaction type silicone adhesives. Among them, addition reaction type silicone adhesives are preferably used from the viewpoint of being curable at low temperature in a short time. Note that these addition reaction type silicone adhesives are cured when the adhesive layer is formed on the support. When an addition reaction type silicone pressure-sensitive adhesive is used as the silicone pressure-sensitive adhesive, the silicone pressure-sensitive adhesive may contain a catalyst such as a platinum catalyst. For example, the addition reaction type silicone adhesive can be cured by, if necessary, diluting a silicone resin solution with a solvent such as toluene, adding a catalyst such as a platinum catalyst, stirring until homogeneous, applying the solution onto a support, and heating at 100 to 130°C for 1 to 5 minutes. If necessary, a crosslinking agent or an additive for controlling adhesive strength may be added to the addition reaction type silicone adhesive, or the support may be subjected to a primer treatment before the adhesive layer is formed.

[0142] Commercially available silicone resins for use in the addition reaction type silicone pressure sensitive adhesive include SD4580PSA, SD4584PSA, SD4585PSA, SD4587LPSA, SD4560PSA, SD4570PSA, SD4600FCPSA, SD4593PSA, DC7651ADHESIVE, DC7652ADHESIVE, LTC-755, LTC-310 (all manufactured by Dow Corning Toray Co., Ltd.), KR-3700, KR-3701, X-40-3237-1, X-40-3240, X X-40-3291-1, X-40-3229, X-40-3323, X-40-3306, X-40-3270-1 (all manufactured by Shin-Etsu Chemical Co., Ltd.), AS-PSA001, AS-PSA002, AS-PSA003, AS-PSA004, AS-PSA005, AS-PSA012, AS-PSA014, PSA-7465 (all manufactured by Arakawa Chemical Industries Co., Ltd.), TSR1512, TSR1516, TSR1521 (all manufactured by Momentive Performance Materials, Inc.), etc. can be mentioned, however, not limited to these.

[0143] (Polarizing plate) The polarizing plate may be made of any material and have any structure. For example, a polarizing plate of this type is widely used in which a TAC (triacetyl cellulose) film is laminated as a protective film on a stretched polyvinyl alcohol film using iodine as an orientation dye. The polarizing plate may have a layer structure on the surface thereof, which layer has a hard coat having substantially no retardation, antiglare, low reflection, antistatic function, etc.

[0144] (Touch Sensor) The touch sensor is a component that detects the touched point when a user touches an image displayed on a screen with a finger or a touch pen, and depending on the sensor technology, examples include a capacitive type, a resistive film type, and a surface wave type using infrared rays or ultrasound. Touch sensors are generally installed in display devices such as liquid crystal display panels and organic electroluminescence (EL) displays. Furthermore, in recent years, there has been a trend to use base films as an alternative to glass substrates, focusing on their flexibility, and it is preferable to use a touch sensor film. Touch sensor films typically include a patterned transparent conductive layer to perform the function of a sensing electrode.

[0145] <Explanation of terms, etc.> Generally, a "sheet" is defined in JIS as a thin, flat product whose thickness is small relative to its length and width, and generally, a "film" is a thin, flat product whose thickness is extremely small relative to its length and width, and whose maximum thickness is arbitrarily limited, and which is usually supplied in the form of a roll (Japanese Industrial Standards; JIS K6900). However, the boundary between a sheet and a film is unclear, and since there is no need to distinguish between the two in the present invention, in the present invention, when it is referred to as a "film", it is intended to include a "sheet", and when it is referred to as a "sheet", it is intended to include a "film".

[0146] In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES

[0147] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0148] <Evaluation method> (1) Normal peel strength A silicone adhesive liquid was prepared by mixing 100 parts by mass of silicone adhesive "SD4580" manufactured by Dow Toray Co., Ltd., 50 parts by mass of toluene, and 0.9 parts by mass of platinum catalyst "NC-25" manufactured by Dow Toray Co., Ltd. In order to stabilize the adhesive strength, the coating was carried out 5 hours after the liquid was prepared. The silicone adhesive liquid was coated onto a 100 μm thick PET film “T100-100” manufactured by Mitsubishi Chemical Corporation with an applicator to a coating thickness of 3 mils, and cured at 100° C. for 3 minutes. The release layer side of the release film was laminated to the silicone adhesive surface using a rubber roller, and then it was stored at room temperature (23°C) for 24 hours, and then cut into a measurement sample of 2.5 cm wide x 15 cm long. The PET film was fixed to a SUS plate with a peel tester chuck at the bottom and a rubber band at the top, and the release film was peeled off from the silicone adhesive layer at 180° and 0.3 m / min using the peel tester, and the peel strength of the release film to the silicone adhesive was measured.

[0149] (2) Residual adhesive strength (evaluation of the migration of the release layer) The silicone adhesive surface that had been peeled off from the measurement sample as described above was pressed onto a cleaned stainless steel plate (60 mm x 150 mm) with a rubber roller. Using Shimadzu Corporation's "EZ Graph," the PET film with the silicone adhesive layer was peeled off from the stainless steel plate at 180° at room temperature (23°C) under conditions of a pulling speed of 0.3 m / min, and the peel strength was measured. The measured peel strength value was taken as the residual adhesive strength.

[0150] (3) Fluorine atom concentration (atom%) in the thickness direction of the release layer Using GC-IB (Gas Cluster Ion Beam) for XPS (X-ray Photoelectron Spectroscopy), the concentration distribution (ratio) of carbon (C), oxygen (O), silicon (Si) and fluorine (F) atoms in the thickness direction of the release layer of the sample film was measured under a constant sputtering rate (sputtering condition setting). In the fluorine atom concentration distribution, the fluorine atomic ratio at the outermost surface (sputtering time 0) was used as the base, and the ratio (t1[75%] / t2[50%]) of the sputtering time required for the fluorine atomic ratio to decrease to 75% of that at the outermost surface (t1[75%]) to the time required for the fluorine atomic ratio to decrease to 50% of that at the outermost surface (t2[50%]) was calculated as a percentage (%). The fluorine (F) atomic ratio (atom%) on the surface of the release layer was also determined. The fluorine (F) atomic ratio is the ratio (atom%) of the amount of fluorine (F) atoms to the total amount of carbon (C), oxygen (O), silicon (Si) and fluorine (F) atoms.

[0151] In this case, the XPS setting conditions are as follows: Equipment: Shimadzu KRATOS ULTRA2 =Analysis conditions= X-ray intensity: AlKα / 15kV・375W Measurement range: 110μΦ Pass energy: 40 eV Charge correction: 284.6eV (C1s) =Sputtering conditions= Ar-GCIB Ar3000+ 5kV, 70 minutes (2 minute intervals, 35 levels)

[0152] <Example 1> The following (A-1) crosslinkable fluorine silicone polymer, the following (B1-1) non-fluorinated silicone crosslinking agent, and the following (C-1) curing catalyst 1 were mixed. After stirring for 1 minute in this high concentration (10 mass%) state and leaving it to stand for 60 minutes to perform pre-crosslinking, a dilution solvent was added to prepare a 3.5 mass% solution a. Stirring and leaving were performed at room temperature (23°C). Then, this was mixed with 3.5 mass% solution b prepared by mixing the following crosslinkable fluorine silicone polymer (A-2), the following fluorinated silicone crosslinking agent (B2-1), the following curing catalyst 2 (C-2), and a dilution solvent in a mass ratio (solution a:solution b) of 1:1 to prepare a coating solution containing two types of crosslinkable fluorine silicone polymers and having a solids concentration of 3.5 mass%. The coating liquid was then applied to one side of a base film (PET film ("T100-50", thickness 50 μm) manufactured by Mitsubishi Chemical Corporation) using a No. 4 bar, and the coating liquid was cured by heat treatment at 150°C for 15 seconds to obtain a release film (sample film) provided with a release layer.

[0153] (Release Layer Composition) Solution A: (A-1) Crosslinkable fluorine silicone polymer (Solid concentration: 10% by mass, viscosity of 10% by mass diisopropyl ether solution: 10 mm 2 / s(25℃) (Ratio of substituents: DM:Si-F(FH):Si-Vi:Si-H=52:46:2:0 (molar ratio), ratio of vinyl groups in R was 1 mol%, ratio of fluorine substituents was 23 mol%, ratio of methyl groups was 76 mol%) 100 parts by mass

[0154] The above abbreviations are as follows: DM: Dimethylsiloxane unit Si-F(FH): Perfluorohexyl-methylsiloxane unit Si-Vi: vinyl-methylsiloxane unit Si-H: Hydrogen-methylsiloxane unit [ka] JPEG0007631839000003.jpg2050JPEG0007631839000004.jpg2472 JPEG0007631839000005.jpg2048

[0155] (B1-1) Non-fluorinated silicone crosslinking agent (Dow Toray Industries, Inc. "3062A") 0.50 parts by weight (C-1) Platinum catalyst 1 (Dow Toray Industries, Inc. "FS XK-3077") 0.50 parts by mass (Dilution solvent) Diisopropyl ether / ethyl acetate (1:1 (mass ratio))

[0156] Solution b: (A-2) Crosslinkable fluorine silicone polymer (Solvent-free type, 85% by mass, viscosity 5100mm 2 / s(25℃))100 parts by mass (Substituent ratio: DM:Si-F(FH):Si-Vi:Si-H=100:47:3.7:0 (molar ratio); among the substituents bonded to Si, the ratio of vinyl groups was 1.2 mol %, the ratio of fluorine substituents was 15.6 mol %, and the ratio of methyl groups was 83.1 mol %). The viscosity of the crosslinkable fluorine silicone polymer (A-2) was lower than that of the above component (A-1). (B2-1) Fluorinated silicone crosslinking agent (Dow Toray Industries, Inc. "Q2-7560") 1.5 parts by weight (C-2) Platinum catalyst 2 (contained in A-2) (Dilution solvent) n-heptane

[0157] <Example 2> A release film (sample film) was obtained in the same manner as in Example 1, except that the blending ratio of solution a and solution b in Example 1 was changed.

[0158] <Example 3> A release film (sample film) was obtained in the same manner as in Example 1, except that no pre-treatment (pre-crosslinking) was performed; that is, the (A-1), (B1-1), and (C-1) components were added to a specified amount of dilution solvent, and stirred and mixed at room temperature for 1 minute until uniform, to prepare a 3.5 mass% solution a, which was then quickly mixed with solution b in a specified blend ratio to obtain a release layer composition.

[0159] <Example 4> A release film (sample film) was obtained in the same manner as in Example 3, except that 2 mass % of solutions c and d were used instead of solutions a and b in Example 3.

[0160] Solution C: (A-3) Crosslinkable fluorine silicone polymer (Solvent type, 15% by mass, viscosity 4.3mm 2 / s(25℃)) 100 parts by mass (Substituent ratio: DM:Si-F(FPO):Si-Vi:Si-H=100:49:1.2:2.4 (molar ratio); among the substituents bonded to Si, the vinyl group content was 0.4 mol %, the fluorine substituent content was 16.1 mol %, the hydrogen atom content was 0.8 mol %, and the methyl group content was 82.8 mol %. Note that the above substituent ratios are the combined substituent ratios of the (A-3) component and the (B2-2) component.) In addition, Si-F(FPO) is as follows. Other abbreviations are as above. [ka]

[0161] (B2-2) Fluorinated silicone crosslinking agent (contained in A-3) (C-3) Platinum catalyst 3 ("CAT-PL-50T" manufactured by Shin-Etsu Chemical Co., Ltd.) 0.5 parts by mass (Dilution solvent) FS Thinner (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0162] Solution d: Solution d was obtained in the same manner as in solution b, except that the dilution solvent was FS thinner (manufactured by Shin-Etsu Chemical Co., Ltd.) The viscosity of the crosslinkable fluorine silicone polymer (A-2) was lower than that of the above component (A-3).

[0163] <Comparative Example 1> A release film (sample film) was obtained in the same manner as in Example 3, except that only solution a was used.

[0164] <Comparative Example 2> A release film (sample film) was obtained in the same manner as in Example 3, except that only solution b was used.

[0165] <Comparative Example 3> A release film (sample film) was obtained in the same manner as in Example 4, except that only solution c was used.

[0166] <Comparative Example 4> A release film (sample film) was obtained in the same manner as in Example 4, except that only solution d was used.

[0167] [Table 1]

[0168] <Consideration> From the above examples and the results of tests conducted by the inventors thus far, it has been found that a release layer formed on at least one side of a base film, which is formed by curing a release layer composition containing at least two or more different (A) crosslinkable fluorosilicone polymers, has excellent light releasability and low migration properties that allow easy peeling from the silicone pressure-sensitive adhesive layer. Moreover, when investigating commonalities among such release layers, it was found that the concentration distribution of fluorine atoms in the thickness direction of the release layer had a characteristic that fluorine was efficiently concentrated on the surface side of the release layer. More specifically, in the fluorine atom concentration distribution obtained as in the above embodiment, when the fluorine atom ratio of the outermost surface (sputtering time 0) is used as a reference, the ratio (t1[75%] / t2[50%]) of the sputtering time (t1[75%]) required for the fluorine atom ratio to decrease to 75% of the outermost surface and the time (t2[50%]) required for the fluorine atom ratio to decrease to 50% of the outermost surface was smaller in the release layer containing two types of crosslinkable fluorine silicone polymers. That is, the decrease in the fluorine atom concentration at the beginning of etching became faster. In contrast, in the release layer containing only one type of crosslinkable fluorine silicone polymer, the ratio (t1[75%] / t2[50%]) was larger. That is, the difference in the fluorine atom concentration between the surface of the release layer and the inside of the release layer that does not contribute to the light release property became smaller.

[0169] On the other hand, in the above-mentioned method for forming the release layer, the following was found. It is presumed that when a release layer composition containing at least two different (A) crosslinkable fluorine silicone polymers is applied onto a film and dried, the more hydrophobic fluorine substituents tend to segregate toward the surface (air interface). On the other hand, the silicone crosslinking agent and catalyst used in combination are not considered to have the same high hydrophobicity as the (A) crosslinkable fluorine silicone polymer due to their molecular structure, and therefore they are not uniformly dispersed in the film, making it difficult to obtain a release layer in a good cured state, or to obtain the desired light releasability. Therefore, in the present invention, first, (A) crosslinkable fluorine silicone polymer, (B) silicone crosslinking agent and (C) curing catalyst are mixed, and then a "pre-treatment" is carried out to cause reaction by stirring and / or standing, and then the pre-treatment composition obtained by the pre-treatment is mixed with a crosslinkable fluorine silicone polymer having a different fluorine substituent ratio, fluorine substituent structure (length, presence or absence of branching, etc.), viscosity or weight average molecular weight to prepare a release layer composition, which has a light release property that is easier to release from silicone pressure sensitive adhesives.It was found that the formation of a coating film with low migration was also achieved. Although the details of this mechanism are unclear, it is speculated that after preparation of the compounded solution, a moderate amount of entanglement (pre-crosslinking) occurs in the compounded solution over time, and that as a result, more fluorine substituents in (A) the crosslinkable fluorine silicone polymer tend to exist on the surface (air interface) side. Also, crosslinkable fluorine silicone polymers with light release properties have a tendency to have low crosslinking reaction efficiency and high migration due to a high ratio of fluorine substituents, long and branched fluorine substituents, and a low ratio of reactive substituents such as vinyl groups. On the other hand, crosslinkable fluorine silicone polymers characterized by a low number of fluorine substituents, a short length of fluorine substituents, and a high ratio of reactive substituents do not reach the desired light release level, but in contrast to crosslinkable fluorine silicone polymers with light release properties, they have a high crosslinking reaction efficiency and tend to harden easily, and therefore are characterized by low migration. It is expected that by mixing two or more different types of cross-linkable fluorine silicone polymers, the cross-linking reaction within the release layer will be promoted while fluorine atoms are unevenly distributed on the surface of the release layer. It is believed that the above-mentioned reasons have made it possible to form a coating film of a release layer having light release and low migration properties.

Claims

1. The composition comprises at least two different types of (A) crosslinkable fluorine-containing silicone polymers, A release layer composition comprising at least one (A) crosslinkable fluorine-containing silicone polymer, which is previously subjected to a crosslinking reaction in a blend liquid, and then at least another (A) crosslinkable fluorine-containing silicone polymer is mixed therein.

2. The release layer composition according to claim 1 , comprising a combination of crosslinkable fluorine-containing silicone polymers (A) that are different in at least one of the ratio of fluorine substituents, the structure of the fluorine substituents, and the viscosity or the weight-average molecular weight.

3. The release layer composition of claim 1 or 2, further comprising (B) a silicone crosslinker and (C) a curing catalyst.

4. 4. The release layer composition according to claim 1, further comprising a silicone crosslinking agent (B) that does not contain a fluorine substituent.

5. 5. A release film comprising: a base film; and a release layer formed on at least one surface of the base film, the release layer being formed by curing the release layer composition according to any one of claims 1 to 4.

6. 6. The release film according to claim 5, wherein the release layer has a fluorine atom content of 3,000 ppm by mol or more and 900,000 ppm by mol or less.

7. 7. The release film according to claim 5, wherein the release layer has an adhesive peel strength of 500 mN / cm or less and a residual adhesive strength of 3,300 mN / cm or more.

8. A method for producing a release layer composition, comprising mixing (A) a crosslinkable fluorine silicone polymer, (B) a silicone crosslinking agent, and (C) a curing catalyst, and then mixing another (A) crosslinkable fluorine silicone polymer different from the (A) crosslinkable fluorine silicone polymer.

9. The method for producing a release layer composition according to claim 8, wherein the other (A) crosslinkable fluorine silicone polymer is different from the other (A) in at least one of the ratio of fluorine substituents, the structure of the fluorine substituents, and the viscosity or the weight average molecular weight.

10. 10. The method for producing a release layer composition according to claim 8, wherein the crosslinkable fluorine silicone polymer (A), the silicone crosslinking agent (B), and the curing catalyst (C) are mixed, and then stirred and / or allowed to stand, and then the other crosslinkable fluorine silicone polymer (A) is mixed.

11. The method for producing a release layer composition according to claim 10, wherein the stirring and / or standing is performed for 1 minute or more.

12. 12. The method for producing a release layer composition according to claim 8, wherein the silicone crosslinking agent (B) is a silicone crosslinking agent that does not contain a fluorine substituent.

13. A method for producing a release film, comprising applying the release layer composition obtained by the method for producing a release layer composition according to any one of claims 8 to 12 to at least one side of a substrate film.

14. A film laminate comprising: a release film according to any one of claims 5 to 7; a silicone pressure-sensitive adhesive layer; and a laminate film having a functional layer, the release film and the laminate film having the functional layer being bonded together via the silicone pressure-sensitive adhesive layer.

15. The film laminate according to claim 14 , wherein the laminate film having a functional layer comprises a base film and a crosslinked resin layer provided on at least one side of the base film.

16. The film laminate according to claim 15, wherein the crosslinked resin layer is formed from a crosslinked resin layer composition containing a conductive polymer and a binder polymer.

17. The film laminate according to claim 15 , wherein the crosslinked resin layer is an easy-adhesion layer for the silicone pressure-sensitive adhesive layer.

18. The film laminate according to any one of claims 14 to 17, wherein the laminate film having a functional layer comprises a base film and another release layer provided on one side of the base film.

19. The film laminate according to claim 18, wherein the other release layer is configured to sequentially comprise: (E) a first layer formed from a silicone composition containing as a main component a silicone polymer that does not contain a fluorine substituent; and (E) a second layer containing a component that has a fluorine substituent.

20. The film laminate according to claim 18, wherein the another release layer is formed from a silicone composition containing (A) a crosslinkable fluorine-containing silicone polymer as a main component.

21. The film laminate according to claim 18, wherein the other release layer is formed from a silicone composition containing, as a main component, (E) a silicone polymer that does not contain a fluorine substituent.

22. A film laminate comprising the release film according to any one of claims 5 to 7, a silicone pressure-sensitive adhesive layer, and a resin film, the resin film being directly bonded to the release film via the silicone pressure-sensitive adhesive layer.

23. 8. A film laminate comprising the release film according to any one of claims 5 to 7, a silicone pressure-sensitive adhesive layer, and a heavy release film, the release film being laminated on one side of the silicone pressure-sensitive adhesive layer and the heavy release film being laminated on the other side of the silicone pressure-sensitive adhesive layer, the heavy release film having a higher peel strength than the release film, the method comprising peeling off the release film, attaching the exposed surface of the silicone pressure-sensitive adhesive layer to an adherend, and then peeling off the heavy release film.

24. The method for using the film laminate according to claim 23, wherein the adherend is an optical component.

25. The method for using the film laminate according to claim 24, wherein the optical component is a polarizing plate or a touch sensor.

26. The method for using the film laminate according to claim 24 or 25, wherein the optical component is an optical component for use in a vehicle.

Citation Information

Patent Citations

  • Release agent composition for silicone adhesive and release sheet using the same

    JP2005060554A

  • Mold release film

    JP2011201035A

  • Silicone adhesive silicone composition for forming differentiated releaser and double sided differentiated release paper or film

    JP2017165893A

  • Silicone release agent composition, release sheet and release film

    JP2020100763A

  • Silicone release agent composition, release sheet and release film

    JP2020100764A